1990
DOI: 10.1212/wnl.40.3_part_1.391
|View full text |Cite
|
Sign up to set email alerts
|

Comparative cognitive effects of anticonvulsants

Abstract: We investigated the neuropsychological effects of carbamazepine, phenobarbital, and phenytoin in 15 partial complex epilepsy patients treated with each drug for 3 months, using a randomized double-blind, triple crossover design. Neuropsychological evaluation at the end of each treatment period included Digit Span, Selective Reminding Test, Digit Symbol, Finger Tapping, Grooved Pegboard, Choice Reaction Time, P3 evoked potential, and Profile of Mood States. Employing anticonvulsant blood levels and seizure freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
0
7

Year Published

1992
1992
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(102 citation statements)
references
References 0 publications
6
89
0
7
Order By: Relevance
“…The specificity of the cognitive effects per drug appeared much more difficult to demonstrate. Recent reviews (9,10) suggest that the cognitive effects of the commonly used AEDs carbamazepine (CBZ) and valproate (VPA) are mild to moderate and do not have a large clinical impact on patients' daily lives, in contrast to the effects of "older" AEDs, in particular phenobarbitone and phenytoin. CBZ and VPA, therefore, are frequently used as the "gold standard" (1 I j to examine the cognitive effects of newer AEDs.…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of the cognitive effects per drug appeared much more difficult to demonstrate. Recent reviews (9,10) suggest that the cognitive effects of the commonly used AEDs carbamazepine (CBZ) and valproate (VPA) are mild to moderate and do not have a large clinical impact on patients' daily lives, in contrast to the effects of "older" AEDs, in particular phenobarbitone and phenytoin. CBZ and VPA, therefore, are frequently used as the "gold standard" (1 I j to examine the cognitive effects of newer AEDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, these were the only significant results from a total of 32 neuropsychological tests, and results were no longer significant when Bonferroni corrections were made. Meador et al (25) found no difference between CBZ and PHT but found that patients taking phenobarbitone performed significantly worse on one test (Digit Symbol) of eight. The remainder of the statistically significant results were found in single studies and are outlined in Table 8.…”
Section: Resultsmentioning
confidence: 99%
“…5) Several clinical studies have reported no significant differences in the cognitive deficits elicited by carbamazepine, phenytoin or valproate treatments, [28][29][30] whereas phenobarbital has been reported to produce greater cognitive deficits than both carbamazepine and phenytoin. 31) Shannon and Love have reported that a single administration of phenobarbital, but not valproate, 30 min before an operant conditioning test impairs the working memory as assessed by spa- The rats were intraperitoneally injected with phenytoin (nϭ6-8), phenobarbital (nϭ8) or valproate (nϭ8-9) 30 min before the daily ECS administrations, and the open-field test was performed 24 h after the last ECS administration. The columns represent the meanϮS.E.M., * pϽ0.05, * * pϽ0.01 in comparison to the sham-ECS administered rats, † pϽ0.05, † † pϽ0.01 in comparison to the repeated ECS-administered rats (one-way ANOVA followed by Bonferroni's test).…”
Section: Discussionmentioning
confidence: 99%